Conductive, Strong and Tough Reduced Graphene Oxide-based composite film for infrared camouflage application. (1st August 2022) - Zhang, Jianwei; Liang, Gengyuan; Xiao, Ying; Zhao, Wenshu; Tang, Jun; Ju, Su; Bai, Shuxin; Pötschke, Petra; Pionteck, Jürgen
Abstract: For graphene-based film, versatility is essential for its potential multi-functional applications. In order to obtain graphene-based films with superior mechanical and electrical properties, a "brick and mortar" structure has been proposed by previous researchers. In this structure, the graphene or reduced graphene oxide (rGO) layers are the "bricks", while the "mortar" is various, which is critical to the performance of the films. In this work, the mixture of carbon nanotube (CNT)/polyurethane (PU) was introduced as the mortar to bind rGO layers, forming a dense layered film. The PU builds strong interactions between rGO layers through covalent bonds, while the CNTs help to highly reduce the inter-layer electrical resistance. Hence, the CNT/PU/rGO film shows an optimized tensile strength of 1193 MPa and an electrical conductivity of 687 S cm −1 . More remarkably, the PU has good compatibility with ionic liquid (IL), and can build internal transport tunnels for IL in the films. IL was further introduced into the composite film. By applying voltage upon the two sides of the film, ion transport across the two sides of the film can be fast and precisely guided. The interaction between IL and the nano-carbon assemblies can tune the infrared emissivity of the composite film, which "function" proposes the film for potential application as a flexible infrared camouflage device. The performance of the infrared camouflage film is investigated in this work.